A new small animal model for simulating a two-stage-revision procedure in implant-related methicillin-resistant Staphylococcus aureus bone infection. Issue 11 (November 2019) - Brunotte, Maximilian; Rupp, Markus; Stötzel, Sabine; Sommer, Ursula; Mohammed, Walid; Thormann, Ulrich; Heiss, Christian; Lips, Katrin S.; Domann, Eugen; Alt, Volker
Highlights: This paper describes a promising setup-up for failed two-stage revision in implant-related infection in a small animal model. Two different MRSA strains with different inoculation doses are capable to induce reinfection in a two-stage revision procedure in a rabbit animal model. This paper proves high survival rates of rabbits in a simulated failure model of two-stage revision of implant-related infection. The established small animal model for simulating a failed two-stage-revision procedure is in concordance with animal welfare. Abstract: Background: Implant-related bone infections with methicillin-resistant Staphylococcus aureus (MRSA) remain a challenge for orthopedic surgeons. This devasting complication may lead to functional impairment and loss of the affected limbs. High failure rates in treatment make improvement of surgical treatment necessary. Beside an already established demanding and costly large animal model, a small animal model of a two-stage revision does not exist, yet. Thus, the purpose of this study was to establish a preclinical small animal model to simulate a two-stage revision in implant-related MRSA infection. Materials and Methods: In twelve rabbits Steel K-wires were implanted into the intramedullary canal of the left tibia, followed by inoculation with MRSA. Two different clinical isolates of MRSA-strains were used in two different concentrations (CFUs; 10 5 and 10 7 colony forming units (CFUs). This led to four groups of three rabbits each. Eleven rabbits survived the whole study period. After four weeks the inoculated K-wires were removed and replaced with vancomycin loaded PMMA-spacers (stage 1). Twenty-eight days later new K-wire implants were placed intramedullary (stage 2). After 84 days all animals were sacrificed. Tibiae were analyzed microbiologically, radiologically and histologically. Results: In every rabbit K-wire associated infection could be established within the first four weeks. After irrigation and debridement at revision one (stage 1), infection could be eradicated in 67% of group I, in 50% of group II and in 33% of group III and IV. Recurrence of the infection could be determined in all animals of group I and IV at day 84. X-ray analysis and histology both demonstrated clear signs of osteomyelitis after twelve weeks. Survival, clinical observations and weight assessment confirmed the ethical justifiable stress of the animals during the experiment. Conclusion: The presented small animal model of a two-stage revision in implant-related infection is a promising preclinical set-up for assessment of new treatment strategies of implant-related infections. Both high survival as well as reinfection rates were possible by simulating the clinical gold standard of two-stage revision surgery in an MRSA implant-related infection model. Therefore, the model can be deemed suitable for further preclinical in vivo testing.